2010
DOI: 10.1016/j.chom.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor Reactivates Human Cytomegalovirus in a Latently Infected Humanized Mouse Model

Abstract: Summary Human cytomegalovirus (HCMV) continues to be a significant cause of morbidity and mortality in organ transplant recipients despite the availability of antiviral therapy. Considerable controversy exists regarding the use of granulocyte-colony stimulating factor (G-CSF) mobilized blood products from HCMV seropositive donors during stem cell transplantation (SCT) and in patients receiving granulocyte transfusions to treat neutropenia. In order to understand mechanisms of HCMV transmission to patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
140
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(146 citation statements)
references
References 33 publications
6
140
0
Order By: Relevance
“…Although studies of infection in humanized mice have only recently begun, this approach promises to provide unprecedented insights into mechanisms of host interaction with human pathogens including hepatitis viruses, HIV, CMV, EpsteinBarr virus, dengue virus, N. meningitidis, and Plasmodium falciparum (e.g., Bente 2005;Jimé-nez-Díaz 2009;Smith et al 2010;Berges and Rowan 2011;Sato et al 2011;Zeisel et al 2011;Melican et al 2013).…”
Section: Humanized Micementioning
confidence: 99%
“…Although studies of infection in humanized mice have only recently begun, this approach promises to provide unprecedented insights into mechanisms of host interaction with human pathogens including hepatitis viruses, HIV, CMV, EpsteinBarr virus, dengue virus, N. meningitidis, and Plasmodium falciparum (e.g., Bente 2005;Jimé-nez-Díaz 2009;Smith et al 2010;Berges and Rowan 2011;Sato et al 2011;Zeisel et al 2011;Melican et al 2013).…”
Section: Humanized Micementioning
confidence: 99%
“…However, human myelopoiesis is not efficient in these models due to a lack of species cross-reactivity of nonhematopoietic cell-derived growth factors including CSF-1, GM-CSF, IL-3, and erythropoietin. This has resulted in poor differentiation and/or function of cells of the monocyte/macrophage lineage unless supported by the addition of human cytokines (22)(23)(24)(25)(26)(27) (28)(29)(30)(31), but whether fully functional specialized myeloid DC subsets develop has not been addressed. Although DC phenotypically resembling human blood CD141 + DC by expression of CD141, CLEC9A, NECL2, and TLR3 were found in spleens of humanized mice, their low frequency has limited functional characterization (7).…”
mentioning
confidence: 99%
“…However, many more hurdles have to be overcome [27,28,88], the manipulation of human immune system components will generate potent preclinical models for relevant human diseases, which might yield results that can be more easily translated into the clinic. Hepatitis B virus (HBV) Liver disease [41] Herpes simplex virus 2 (HSV-2) Inflammation at mucosal infection site [16] Human cytomegalovirus (HCMV) GM-CSF mediated reactivation from myeloid cells [17] Epstein Barr virus (EBV) Tumor formation, hemophagocytic lymphohistiocytosis, erosive arthritis [89] Kaposi Sarcoma associated herpesvirus (KSHV) Persistent infection in B cells [39] Adenovirus Liver disease [40] Human immunodeficiency virus (HIV) CD4 + T cell depletion [43] Human T cell leukemia virus 1 (HTLV-1)…”
Section: Discussionmentioning
confidence: 99%
“…Among the -herpesviruses, human cytomegalovirus (HCMV) infection was explored in huNSG mice [17]. In a first study HCMV was found to infect the reconstituted human myeloid compartment and could be reactivated from it by G-CSF treatment.…”
Section: Herpesvirus Infections (Hsv Hcmv Ebv Kshv)mentioning
confidence: 99%
See 1 more Smart Citation